Nephroprotective Effect of Metformin on Gentamicin Induced Renal Injuries in Rats (Medical Forum Monthly, 2023)
Objective: Metformin, an oral anti-diabetic agent has been studied in the past for its protective effects as an antioxidant. The study was conducted to compare the nephroprotective effects of two doses of metformin in aminoglycoside induced renal injuries in Sprague-Dawley rats.Study Design: experimental studyPlace and Duration of Study: This study was conducted at the Department of Pharmacology, ANMCH, Islamabad, Pakistan in collaboration with the animal house of National Institute of Health (NIH),Islamabad, Pakistan from July 2015 to December 2015.Materials and Methods: 30 adult male Sprague-Dawley rats weighing 200 ± 50 g, kept under similar conditions for food and temperature, were randomly divided into three groups of Gentamicin treated control (C), Gentamicin & low dose Metformin treated 1 (M1) and Gentamicin & high dose Metformin treated 2 (M2). Renal failure was induced by injecting gentamicin (80mg/kg/day) intraperitoneally for eight days followed by oral metformin for 28 days. Sampling for serum creatinine, 24 hour urinary volume and 24 hour urinary proteins was done at day 0, 14 and 28.Results: It was found that metformin administration in gentamicin induced renal failure results in significantly increased urinary output, reduced creatinine levels along with significantly decreased urinary proteins in M2 group as compared to M1 group. While in group C, all parameters of renal failure were increased.Conclusion: Metformin in a dose of 150mg/kg prevents aminoglycoside-induced renal injuries in rats.